The effect of cocoa consumption on the anthropometric outcomes in overweight and obese subjects: A time and dose–response meta-analysis of randomized controlled trials - Abu-Zaid, Ahmed; Prabahar, Kousalya; Hernández-Wolters, Benjamin; Jamilian, Parmida; Alyoubi, Reem Abdullah; Alyahyawi, Naseem; Mazi, Ahlam; Alkahmous, Alhassna Ali Mohamed; Kord-Varkaneh, Hamed (Journal of functional foods, 2024)
[Display omitted] •Cocoa consumption significantly decreased body weight, BMI, and WC•Cocoa consumption resulted in lowered body weight in dosages ≤20 g/day.•Cocoa consumption resulted in lowered body weight in treatment duration ˃4 weeks. Inconsistencies are evident within the literature regarding the effect of cocoa consumption on anthropometric outcomes. To address the influence of cocoa consumption on weight, body mass index (BMI), and waist circumference (WC) in overweight and obese subjects we conducted a time and dose–response meta-analysis of randomized controlled trials (RCTs). Scopus, Web of Science, Embase, and PubMed/Medline were searched for relevant articles from inception until July 11, 2023. The random effects method meta-analysis compared changes in anthropometric outcomes in participants Results are displayed as weighted mean difference (WMD) with 95 % confidence interval (CI). 19 RCTs were included in the present meta-analysis. Cocoa consumption significantly decreased body weight (WMD: −0.26 kg, 95 % CI: −0.49 to −0.02, P = 0.028), BMI (WMD: −0.16 kg/m2, 95 % CI: −0.30 to −0.02, P = 0.021), and WC (WMD: −0.69 cm, 95 % CI: −1.35 to −0.03, p = 0.038). In subgroup analyses, cocoa consumption resulted in lowered body weight in dosages ≤20 g/day (WMD: −0.33 kg), and treatment duration ˃4 weeks (WMD: −0.35 kg). In the non-linear dose–response assessment, a negative correlation was found between cocoa consumption dose (up to 50 g/day) and changes in WC (P = 0.001) and body weight (P = 0.0007). Cocoa consumption is associated with a reduction in BMI, weight, and WC in overweight and obese subjects; however, statistically significant effects were only detected in doses less than 20 g/day and interventions longer than 4 weeks.